Referential communication in people with recent-onset schizophrenia-spectrum disorders - Achim, Amélie M.; Achim, André; Fossard, Marion (Frontiers in Psychiatry, 2022)
People with schizophrenia present with language production impairments, yet very few studies examine language production in the context of collaborative, verbal interaction tasks performed with a real interaction partner. The current study relied on a referential communication paradigm in which participants with schizophrenia (SZ) and healthy controls (HC) presented a series of movie characters to their interaction partner, whose role was to identify and place the characters in the same order. The HC spontaneously provided more information when presenting characters that their interaction partner was unlikely to know than when presenting very well-known characters, and the magnitude of this adjustment was positively correlated with their performance on a theory of mind task. In contrast, people with SZ showed a significantly reduced (absent) adjustment to the likely-known versus likely-unknown nature of the characters, and no correlation emerged with ToM. Further examination of the verbal productions revealed that HC often combined movie-related information (ex: character’s name or movie title) and descriptive information whereas people with SZ more often used description only to present the characters. Overall, this study adds to our knowledge about referential choices in SZ in the context of collaborative verbal interactions with a real interaction partner.